Selective Detection of Lysozyme Biomarker Utilizing Large Area Chemical Vapor Deposition-Grown Graphene-Based Field-Effect Transistor - Ghosh, Sujoy; Khan, Niazul I.; Tsavalas, John G.; Song, Edward (Frontiers in Bioengineering and Biotechnology, 2018)
Selective and rapid detection of biomarkers is of utmost importance in modern day health care for early stage diagnosis to prevent fatal diseases and infections. Among several protein biomarkers, the role of lysozyme has been found to be especially important in human immune system in order to prevent several bacterial infections and other chronic disease such as bronchopulmonary dysplasia. Thus, real time monitoring of lysozyme concentration in human body can pave a facile route for early warning for potential bacterial infections. Here, we present for the first time a label-free lysozyme protein sensor that is rapid and selective based on a graphene field-effect transistor (GFET) functionalized with selectively designed single-stranded probe DNA (pDNA) with high binding affinity toward lysozyme molecules. When the target lysozyme molecules bind to the surface-immobilized pDNAs, the resulting shift of the charge neutrality points of the GFET device, also known as the Dirac voltage, varied systematically with the concentration of target lysozyme molecules. The experimental results show that the GFET-based biosensor is capable of detecting lysozyme molecules in the concentration range from 10 nM to 1 µM.